Home bias in humanitarian aid: The role of regional favoritism in the allocation of international disaster relief - Christian Bommera; Axel Dreher; Marcello Pérez-Alvarez (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2019)
Natural disasters represent a major challenge for human welfare across the globe. Given the prominent role of international humanitarian aid in alleviating human suffering, the investigation of its determinants is of paramount importance. While existing studies show its allocation to be influenced by donors' foreign policy considerations, domestic political factors within recipient countries have not been systematically explored. This paper addresses this important research gap by investigating whether regional favoritism shapes humanitarian aid flows. Using a rich and unique dataset derived from reports of the Office of US Foreign Disaster Assistance (OFDA), we show that substantially larger amounts of aid are disbursed when natural disasters hit the birth region of the recipient countries' political leader. While we find no evidence that US commercial or political interests affect the size of this home bias, the bias is stronger in countries with a weaker bureaucracy and governance, suggesting the absence of effective safeguards in the allocation of aid.
Keywords: 330; humanitarian aid; natural disasters; regional favoritism; birth regions